2021
DOI: 10.3390/plants10102206
|View full text |Cite
|
Sign up to set email alerts
|

Application of K and Zn Influences the Mineral Accumulation More in Hybrid Than Inbred Maize Cultivars

Abstract: Maize (Zea mays L.) is an important crop used for feeding humans and cattle globally. Deficiency of potassium (K) and zinc (Zn) adversely impacts the maize crop productivity and quality. However, the application of these nutrients shows variant responses in different maize cultivars. To understand this perspective, the current study aimed at investigating K and Zn’s optimal concentration in different hybrid and inbred maize cultivars. The treatments were based on three zinc levels (0, 6, and 12 mg Zn kg−1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Previous studies have also reported that foliar application of Zn affects yield and agronomic traits, enhancing the number of pods per plant Banks 84 . These results align with studies that suggest Co and Zn applications can enhance plant biomass, enzymatic actions, and physiological and chemical processes, leading to improved transpiration rates 85 , 86 . Therefore, applying the combined applications of Co + Znfol improved plant performance, growth, and nutrient uptake.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have also reported that foliar application of Zn affects yield and agronomic traits, enhancing the number of pods per plant Banks 84 . These results align with studies that suggest Co and Zn applications can enhance plant biomass, enzymatic actions, and physiological and chemical processes, leading to improved transpiration rates 85 , 86 . Therefore, applying the combined applications of Co + Znfol improved plant performance, growth, and nutrient uptake.…”
Section: Discussionsupporting
confidence: 89%
“…It might be associated with the improved relative water content (RWC) and osmotic potential ( Fanaei et al., 2009 ). Application of Zn also improved the chlorophyll content in maize ( Raza et al., 2021 ), soybean ( Weisany et al., 2012 ), and wheat ( Sharma et al., 2005 ). In addition, photosynthetic rates, transpiration rates, and stomatal conductance were also improved possibly through the involvement in guard cell movement and osmoregulation that ultimately enhanced the stomatal conductance ( Imtiaz et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, photosynthetic rates, transpiration rates, and stomatal conductance were also improved possibly through the involvement in guard cell movement and osmoregulation that ultimately enhanced the stomatal conductance ( Imtiaz et al., 2023 ). K application has also been reported to enhance the gas exchange in plants as well as opening and closing of stomata, especially in cauliflower ( Sharma et al., 1994 ) and maize ( Raza et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations